Dianetics - "Hubbard,L.Ron" (Los Angles, 2008)
Originally written and published in national magazines to coincide with the release of "Dianetics: The Modern Science of Mental Health", here is L. Ron Hubbard's own story of his developmental trail and two-decade journey to the discovery of the Reactive Mind. "Evolution of a Science" contains the only account of: How the optimum computing machine - the mind - works, How Mr. Hubbard discovered Basic Personality, How the Dynamic Principle of Existence - SURVIVE! - was first isolated, How wrong answers enter into the mind and are held down, giving further wrong answers, How there seem to be 'Demons' of the mind, How the engram was discovered, and How Dianetics techniques were developed. That's why "Evolution of a Science" is the story of the greatest adventure of all - the exploration that discovered the Reactive Mind and the technology to conquer it. He wrote it so you would know.
Keywords: Dianetics